PROTECTIVE EFFECT OF ALCOHOLIC EXTRACT OF BAUHINIA VARIEGATA IN RAT CEREBRAL ISCHEMIA/REPERFUSION INDUCED OXIDATIVE STRESS - MARASANI ANIL (International Journal of Pharma and Bio Sciences, 2014)
Stroke is the second leading cause of death. Ischemia leads to cellular dysfunction and necrosis. Wistar albino rats were treated with alcoholic extract of Bauhinia variegata (200 and 400 mg/kg; p.o) for 15 days prior to Ischemia/Reperfusion. Ascorbic acid (50 mg/kg) was used as a reference standard. Ischemia/Reperfusion was induced by occluding common carotid arteries for 25 min, followed by 40 min reperfusion. Ischemia/Reperfusion caused significant depletion in superoxide dismutase, catalase, glutathione and significant increase in LPO in brain homogenate. All the alterations induced by cerebral ischemia were significantly attenuated by pretreatment with bark extract at the doses of 200 and 400 mg/kg, and the effect was comparable to that of ascorbic acid (p value < 0.05). In conclusion alcoholic bark extract containing the flavonoids and phenolic antioxidants was found to protect rat brain against Ischemia/Reperfusion induced oxidative stress, and the observed effect may be attributed to its antioxidant properties.